2009
DOI: 10.1007/s10067-009-1283-z
|View full text |Cite|
|
Sign up to set email alerts
|

Rarely occurring mutation of ACVR1 gene in Moroccan patient with fibrodysplasia ossificans progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP, MIM 135100) is a rare autosomal dominant disorder characterized by postnatal progressive heterotopic ossification of the connective tissue and congenital malformation of the big toes. Recently, FOP has been associated with a specific mutation of ACVR1, the gene coding for a bone morphogenetic protein type I receptor. We report the case of a Moroccan patient with FOP carrying a rarely occurring mutation of ACVR1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…She developed rapidly progressive heterotopic ossification at 12 years of age. Other novel alleles have also been described from specific regions around the world, for example, c.774G>T; p.Arg258Ser in Turkey, Spain, and Morocco (Ratbi et al, 2010;Morales-Piga et al, 2012;Eresen Yazıcıoglu et al, 2013), c.605G>T; p.Arg202Ile in the United Kingdom (Petrie et al, 2009), and c.983G>A; p.Gly328Glu in Brazil (Connor & Evans, 1982;Kaplan et al, 2009;Carvalho et al, 2010;Stefanova et al, 2012). All of these reported variant alleles were found between exons 6 and 9 of ACVR1 (Table 2).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…She developed rapidly progressive heterotopic ossification at 12 years of age. Other novel alleles have also been described from specific regions around the world, for example, c.774G>T; p.Arg258Ser in Turkey, Spain, and Morocco (Ratbi et al, 2010;Morales-Piga et al, 2012;Eresen Yazıcıoglu et al, 2013), c.605G>T; p.Arg202Ile in the United Kingdom (Petrie et al, 2009), and c.983G>A; p.Gly328Glu in Brazil (Connor & Evans, 1982;Kaplan et al, 2009;Carvalho et al, 2010;Stefanova et al, 2012). All of these reported variant alleles were found between exons 6 and 9 of ACVR1 (Table 2).…”
Section: Discussionmentioning
confidence: 90%
“…In addition to this, some novel allelic variants in the ACVR1 gene have been described among other populations; these include c.774G>T; p.Arg258Ser in Turkey, Spain, and Morocco (Ratbi et al, 2010;Morales-Piga et al, 2012;Eresen Yazıcıoglu et al, 2013), c.605G>T; p.Arg202Ile in the UK (Petrie et al, 2009) and c.974G>C; p.Gly325Ala in the United States (Whyte et al, 2012), c.1067G>A; p.Gly356Asp in Japan, Germany, and China (Furuya et al, 2008;Kaplan et al, 2009;Stefanova et al, 2012;Zhang et al, 2013), and c.983G>A; p.Gly328Glu in Brazil, Great Britain, and Germany (Connor & Evans, 1982;Kaplan et al, 2009;Carvalho et al, 2010;Stefanova et al, 2012). The ACVR1 gene encodes a protein located at the cell membrane which acts as a receptor for BMP ligands (Nakahara et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Carvalho et al (2010) suggested that variant FOP phenotypes are associated with specific mutations in ACVR1 gene. Ratbi et al (2010) reported the case of a Moroccan patient with FOP carrying a rarely occurring mutation at c.774G>T of ACVR1 gene. Bocciardi et al (2009) reported the c.617G>A mutation, leading to the p.R206H substitution in the ACVR1 gene in 15 out of 17 Italian patients.…”
Section: Acvr1/alk2mentioning
confidence: 99%
“…Fibrodysplasia ossificans progressiva (FOP) is a rare autosomal dominant disorder of dysregulated cellular differentiation, which is characterized by congenital malformation of the great toes during embryonic skeletal development and by progressive heterotopic endochondral ossification of the connective tissue post-natally that forms qualitatively normal bone in characteristic extraskeletal sites (Ratbi et al, 2010;Pignolo et al, 2011;Chakkalakal et al, 2012). Extra-skeletal bone formation associated with inflammation preceding the osseous conversion usually begins in the first decade, predominantly in the head, neck, and shoulders (Kartal-Kaess et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So far, 13 missense mutations and a 3-base deletion mutation have been found in FOP, and the detailed types and phenotypes of common mutations are shown in Table 1 (2,7,10,13,14).…”
Section: Mutations and Diagnosismentioning
confidence: 99%